Effect on Local Structure and Phase Transition of Perovskite-Type [N(CH3)4]2Zn1-x Cu x Br4 (x = 0, 0.5, 0.7, and 1) Crystals with the Various Doping of Cu2+ Ions - Ae Ran Lim (Nature Portfolio, 2018)
Abstract This study focused on how the local structures in pure [N(CH3)4]2ZnBr4 crystal are affected by the partial replacement of Zn2+ ions with Cu2+ ions. The structures and phase transition temperatures TC of perovskite-type [N(CH3)4]2Zn1-x Cu x Br4 (x = 0, 0.5, 0.7, and 1) mixed crystals were almost unchanged by the partial doping of Cu2+ ions. The environments for the local structures of [N(CH3)4]2Zn1-x Cu x Br4 mixed systems were studied according to differences in the chemical shifts of the 1H magic angle spinning (MAS) NMR, 13C cross-polarization (CP)/MAS NMR, and 14N NMR spectra. The 1H and 13C NMR results showed that the local environments of 1H and 13C nuclei near TC are not affected by substituting Zn2+ ions with Cu2+ ions, whereas the 14N NMR results showed that the local environment is affected near TC. Consequently, the main indicators of the phase transition in [N(CH3)4]2Zn1-x Cu x Br4 are related to the ferroelastic characteristics with different orientations.